Systematic review and meta-analysis of Internet interventions for smoking cessation among adults - Graham AL; Carpenter KM; Cha S; Cole S; Jacobs MA; Raskob M; Cole-Lewis H (Dove Medical Press, 2016)
Amanda L Graham,1,2 Kelly M Carpenter,3 Sarah Cha,1 Sam Cole,3 Megan A Jacobs,1 Margaret Raskob,3 Heather Cole-Lewis,4,51Schroeder Institute for Tobacco Research and Policy Studies, Truth Initiative, Washington, DC, 2Department of Oncology, Georgetown University Medical Center/Cancer Prevention and Control Program, Lombardi Comprehensive Cancer Center, Washington, DC, 3Alere Wellbeing, Seattle, WA, 4Johnson & Johnson Health and Wellness Solutions, Inc., New Brunswick, NJ, 5ICF International, Rockville, MD, USA Background: The aim of this systematic review was to determine the effectiveness of Internet interventions in promoting smoking cessation among adult tobacco users relative to other forms of intervention recommended in treatment guidelines. Methods: This review followed Cochrane Collaboration guidelines for systematic reviews. Combinations of “Internet,” “web-based,”and “smoking cessation intervention” and related keywords were used in both automated and manual searches. We included randomized trials published from January 1990 through to April 2015. A modified version of the Cochrane risk of bias assessment tool was used. We calculated risk ratios (RRs) for each study. Meta-analysis was conducted using random-effects method to pool RRs. Presentation of results follows the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Results: Forty randomized trials involving 98,530 participants were included. Most trials had a low risk of bias in most domains. Pooled results comparing Internet interventions to assessment-only/waitlist control were significant (RR 1.60, 95% confidence interval [CI] 1.15–2.21, I2=51.7%; four studies). Pooled results of largely static Internet interventions compared to print materials were not significant (RR 0.83, 95% CI 0.63–1.10, I2=0%; two studies), whereas comparisons of interactive Internet interventions to print materials were significant (RR 2.10, 95% CI 1.25–3.52, I2=41.6%; two studies). No significant effects were observed in pooled results of Internet interventions compared to face-to-face counseling (RR 1.35, 95% CI 0.97–1.87, I2=0%; four studies) or to telephone counseling (RR 0.95, 95% CI 0.79–1.13, I2=0%; two studies). The majority of trials compared different Internet interventions; pooled results from 15 such trials (24 comparisons) found a significant effect in favor of experimental Internet interventions (RR 1.16, 95% CI 1.03–1.31, I2=76.7%). Conclusion: Internet interventions are superior to other broad reach cessation interventions (ie, print materials), equivalent to other currently recommended treatment modes (telephone and in-person counseling), and they have an important role to play in the arsenal of tobacco-dependence treatments. Keywords: systematic review, meta-analysis, Internet, smoking cessation, tobacco control